The Karabakh Conflict Between Armenia and Azerbaijan - Yavuz, M. Hakan. author. aut Link
IX, 225 p. 3 illus., 2 illus. in color.
Keywords: “This is a comprehensive and timely study by two eminent political scientists, Professors Yavuz and Gunter, on the recent war over Nagorno-Karabakh. It is essential reading for anyone interested in ethnic conflict and the failure of the international system of conflict resolution, specifically the so-called OSCE’s Minsk Group. In eight detailed chapters the authors deal with the history, causes and consequences of the war, expertly covering the failed diplomacy. They also approach future peace prospects in a rational and realistic manner.” --Ozay Mehmet, Distinguished Research Professor Emeritus, Carleton University, Ottawa “The Nagorno-Karabakh conflict has significant relevance for ethnic conflict studies in general, post-Soviet conflict studies in particular, and great power struggles involving Russia, Turkey, Iran, and even further afoot the United States and the European Union. Yavuz and Gunter’s cause, event, and consequence methodology eases the difficulty of making sense of a very complex situation. Moreover, their multi-disciplinary narrative includes not just Caucasian history but brings in a deep understanding and explanation of international law, “clash of civilizations” theory, diaspora narratives, great power proxy involvement, and media perception and manipulation. In doing so, they open new avenues for understanding these important events and issues going forward.” --Edward Erickson, Professor of Military History Emeritus, Department of War Studies, U.S. Marine Corps University This project deals with the historical, social and political aspects of the Karabakh issue regarding its origins, development and the current status of the conflict and its precedents and implications for other secessionist wars subsequent to the war in the autumn of 2020. This book also explores the international legal precedents of self-determination versus territorial integrity and the latest successful weapons developments lessons from the recent war involving drones and Azerbaijan’s rich oil reserves. M. Hakan Yavuz is Professor of Political Science at the University of Utah, USA. Michael M. Gunter is Professor of Political Science at Tennessee Technological, University in Cookeville, USA.